Analisis Perbandingan Kinerja Keuangan PT. Telkom, Tbk dengan PT. Indosat, Tbk Periode 2005 - 2010 - Rudianto, Dudi (Business and Management Review, 2011)
PT. Telkom Tbk. (TLKM) and PT. Indosat Tbk. (ISAT) are the two giants that dominate the telecommunications company and is consistently monopolize the mobile telecommunications industry in Indonesia. Both companies have strengths and weaknesses of each of the services provided to its customers. Competition in both mobile operators the company was committed in the fight over the very prospect of Indonesia to maintain and increase its market share respectively. One important aspect to consider for investors in making investment strategy is to look at the company's financial performance. Overall financial performance of PT. Telkom Tbk, which is measured by QR, DAR, ROE, ROA, NPM, TATO and PBV have better performance than the PT. Indosat Tbk. While the views of different test using one way ANOVA test was partially obtained results that except for QR, and other financial performance measures for the two companies is different. But through testing simultaneously obtained results that the overall financial performance measures that compare the two companies did not have differences. It means that the two companies do not have a great potential to set up a portfolio of investment strategies that will be formed by the investor. Keywords: Financial performance, quick ratio (QR), debt to assets ratio (DAR), return on equity (ROE), return on assets (ROA), net profit margin (NPM), total assets turnover (TATO), and price to book value (PBV)